Pengaruh Pelatihan Kerja Terhadap Kinerja Karyawan Pada PT Kusumatama Mitra Selaras Jakarta - Rani Kurniasari; Nurvi Oktiani; Gema Ramadhanti (Universitas Bina Sarana Informatika, 2018)
ABSTRACT: One of the important factors in improving the quality of Human Resources (HR) is by training and developing employees to achieve company goals. This research method uses quantitative methods, with the technique of determining saturated sampling. The research was conducted through questionnaires to all employees of PT. Kasumatama Mitra Selaras, which is an outsourcing company with a total of 37 respondents. This questionnaire calculation with the technique of calculating the correlation coefficient, the coefficient of determination and multiple linear regression equations. With the SPSS 21 application, the correlation coefficient results are 0.650 and the results are categorized as strong. the determination coefficient can be seen that 0.422 or 42.2% of PT Kusumatama Mitra Selaras performance variables can be influenced by the training variable and the remaining 57.8% is influenced by other factors. Based on the calculation table of the regression equation can be obtained the equation is Y = 13.155 + 0.662 X. From the equation of the function it can be said that if training is constant or is 0 then Y (Performance) is equal to 13.155 with a regression coefficient of 0.662.